Cimicids of Medical and Veterinary Importance - Fatima Zohra Hamlili; Jean Michel Bérenger; Philippe Parola (Insects, 2023)
Members of the Cimicidae family are significant pests for mammals and birds, and they have attracted medical and veterinary interest. A number of recent studies have investigated bed bugs, due to their dramatic resurgence all over the world. Indeed, bed bugs are of significant public health and socioeconomic importance since they lead to financial burdens and dermatological complications and may have mental and psychological consequences. It is important to note that certain cimicids with a preference for specific hosts (birds and bats) use humans as an alternative host, and some cimicids have been reported to willingly feed on human blood. In addition, members of the Cimicidae family can lead to economic burdens and certain species are the vectors for pathogens responsible for diseases. Therefore, in this review, we aim to provide an update on the species within the Cimicidae family that have varying medical and veterinary impacts, including their distribution and their associated microorganisms. Various microbes have been documented in bed bugs and certain important pathogens have been experimentally documented to be passively transmitted by bed bugs, although no conclusive evidence has yet associated them with epidemiological outbreaks. Additionally, among the studied cimicids (bat bugs, chicken bugs, and swallow bugs), only the American swallow bug has been considered to be a vector of several arboviruses, although there is no proven evidence of transmission to humans or animals. Further studies are needed to elucidate the reason that certain species in the Cimicidae family cannot be biologically involved in transmission to humans or animals. Additional investigations are also required to better understand the roles of Cimicidae family members in the transmission of human pathogens in the field.